The effect of Ganoderma boninense infection on the expressions of thiamine (vitamin b1) biosynthesis genes in oil palm - Balia Yusof, Zetty Norhana; Borhan, Farrah Payyadhah; Mohamad, Fatimatul Azma; Rusli, Mohd Hefni (Malaysian Palm Oil Board, 2015)
Thiamine pyrophosphate (TPP), an active form of thiamine plays a fundamental role as an enzymatic cofactor in universal metabolic pathways including glycolysis and pentose phosphate pathway. We identified and amplified gene transcripts of the first two enzymes in the pathway, THI1/THI4 and THIC. Primers were designed based on sequence comparison of the genes from Arabidopsis, rice and maize. We also investigated the relationship between expression of thiamine biosynthesis genes and stress. This is due to findings suggesting that TPP has functions other than as a cofactor in response to stress in plants. The response of THI1/THI4 and THIC gene transcripts towards the infection of Ganoderma boninense on oil palm was observed. The gene transcripts’ expressions were analysed via RT-PCR over a time course after infection. For THI1/THI4, the percentage of level of expression for healthy oil palm is 29.79% and an increase up to 70.21% was observed in artificially infected oil palm seedlings. For THIC gene, in healthy oil palm, the level of expression was 45.83% but when infected, it increased slightly up to 54.17%. Our results support the suggestion that thiamine may play an important role in the protection of cells against stress as it leads to an overexpression of thiamine in general.